Pengaruh Penerapan Media Augmented Reality Eco-Ar 1-3 Berbasis Model Discovery Learning Untuk Meningkatkan Pemahaman Konsep Ekologi - Cornelia Zanindita1; Puguh Karyanto1; Dewi Puspitasari1; Ristanti Yustin2 (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
The purpose of this research is to determine influence of implementation of Augmented Reality ECO-AR 1-3 media based on Discovery Learning model to improve ecological concept. This research is included in ex post facto research with quantitative approach. The subjects of the study were students of class X MIPA 2 and XI MIPA 7 each class consist of 35 students. Research sampling technique used cluster random sampling. The research design used post-group design. Data obtained from NEP and posttest questionnaire. Data collection used tests, documentation, observation, and questionnaires. The research procedure includes preparation, execution, data processing and completion. Validity test and instrument reliability test using Alpha Cronbach formula with counted by SPSS 21 program. Data analysis technique used normality test, homogeneity test, and non-paired samples T test with 5% significance level. Augmented Reality ECO-AR 1-3 media based on Discovery Learning using non-paired sample t-test has significance result on knowledge and attitude aspect less than 0,05 so that H0 is rejected. H0 rejected indicate difference of effectiveness between environmental literacy result from class XI MIPA 7 subject with class X MIPA 2. The result of research shows that there is an increase in anti-anthropocentrism aspect and the highest result in aspect of limit to growth.